Surgical treatment of odontogenic keratocyst associated with cryotherapy with refrigerant gas: 10-year follow-up (Research, Society and Development, 2022)
Odontogenic keratocyst (OKC) is an intraosseous cystic lesion, being one of the most common cysts of the gnathic bones, responsible for 3% to 11% of all odontogenic cysts. This cyst has high recurrence rates, from 5 to 62%, and usually occurs within the first 5 years, and may be directly linked to the type of technique used to treat the lesion. The forms of treatment for OKC may vary according to its clinical and imaging presentation. Considering the high recurrence rates of this benign pathology, only enucleation may not be enough, so other forms of adjuvant treatment are proposed, such as cryotherapy. This case report aims to present the case of a 22-year-old female patient who presented an odontogenic keratocyst (OKC) in the right mandible diagnosed in 2012. Surgical treatment of enucleation and adjuvant treatment with cryotherapy using refrigerant gas were performed. The patient has been followed up for 10 years, without complaints and has not had any recurrence of the cyst.